Transforming Christian Education in the Digital Era: Adapting Inclusive Content through Universal Design for Learning (UDL) - Favor Adelaide Bancin (PT FORMOSA CENDEKIA GLOBAL, 2026)
Digital transformation has changed the way learners learn, interact, and access knowledge. In the context of Christian Religious Education (PAK), this change presents both challenges and opportunities to realize inclusive learning for all students, including those with diverse learning needs. This article aims to examine the adaptation of PAK content for digital-based inclusive learning through the Universal Design for Learning (UDL) 3.0 framework and examine its theological and pedagogical implications. This study uses a literature study method by analyzing various literature on inclusive education, digital technology, Universal Design for Learning, and Christian Religious Education. The results of the study show that the principles of UDL, namely engagement, representation, and action and expression, can be effectively integrated in PAK learning through the use of digital technology and a student-centered pedagogical approach.